Предмет: Алгебра,
автор: aneshkasolnce
помогите пожалуйстаа
Приложения:
Ответы
Автор ответа:
0
а) ab * (6a^2 b - 2b^2) - (3a^3 - 2ab) * 2b^2
= 6a^3 b^2 - 2ab^3 - 6a^3 b^2 + 4ab^3 = -2ab^3 + 4ab^3 = 2ab^3
б) a (2 - 3w^2 - 4w^4) + (3 + 4w^2) * aw^2 = 2a - 3aw^2 - 4aw^4 + 3aw^2 + 4aw^4 = 2a
в) a^2 g^2 * (a - 4c^2 g + 2ac^2 g) - (-2a ^2 g^2 + a^2 c^2 g^2) * 2ag = a^3 g^2 - 4a^2 c^2 g^3 + 2a^3 c^2 g^3 + 4a^2 c^2 g^3 - 2a^3 c^2 g^3 = a^3 g^2
= 6a^3 b^2 - 2ab^3 - 6a^3 b^2 + 4ab^3 = -2ab^3 + 4ab^3 = 2ab^3
б) a (2 - 3w^2 - 4w^4) + (3 + 4w^2) * aw^2 = 2a - 3aw^2 - 4aw^4 + 3aw^2 + 4aw^4 = 2a
в) a^2 g^2 * (a - 4c^2 g + 2ac^2 g) - (-2a ^2 g^2 + a^2 c^2 g^2) * 2ag = a^3 g^2 - 4a^2 c^2 g^3 + 2a^3 c^2 g^3 + 4a^2 c^2 g^3 - 2a^3 c^2 g^3 = a^3 g^2
Похожие вопросы
Предмет: Математика,
автор: lilirosee20
Предмет: Қазақ тiлi,
автор: damiryt75
Предмет: Английский язык,
автор: adilhanovaajza
Предмет: История,
автор: tal14
Предмет: Химия,
автор: Аноним